Crack behavior of heat treated sintered steel under cyclic loading / Al Emran Ismail - Ismail, Al Emran (2003)
Fatigue crack nucleation and initiation at particles or defects in materials have been the interest of many researchers over the past years . This is because the understanding of theses phenomena would provide a better understanding of production of new fatigue resistanc e materials. In this study a test was developed to evaluate the fatigue properties and to observe fatigue crack nucleation and initiation in sintered steel. The fatigue test was carried out on polished specimens which was based on plate bending gives balanced biaxial tension. The experimental results shows that there were mixed mode of crack nucleation and initiation such that most cracks initiated at the interface of particles and matrix especially at high stress values . Cracks were also observed to initiate at voids and beneath the surface. Quenched specimens which were tempered between temperature range of 300°C and 600°C shows similar crack initiation mechanisms. The significant differenc e between as-rece ived and tempered specimens was that the number of cycles to fail due to di fferences in material hardne ss and internal defect s. The result s of the experimentation are discussed in the light of possible micro crack toughening at the crack tip and the presence of residual stresses due, to temperature changes. It is believed that some effects of residual stresses at the surface and beneath playa role in the nucleation of crack in sinter ed steel.